Diagnostic and prognostic significance of apelin-13, APJ for sepsis in the emergency department: A prospective study - Miaomiao Wang; Qian Gao; Shubin Guo (Heliyon, 2024)
Objectives: This study aimed to assess the diagnostic, risk stratification, and prognostic capabilities of apelin-13 and APJ in comparison to procalcitonin (PCT) for septic patients presenting to the emergency department (ED). Methods: Two hundred and thirty-eight patients meeting the Third International Consensus Definition (Sepsis-3) criteria were enrolled from Beijing Chaoyang Hospital's ED, along with a control group of forty healthy individuals. Patients were categorized into two groups based on disease severity: those with sepsis or septic shock. Plasma levels of apelin-13, CD4+ Th cells, and PCT were measured. The expression levels of plasma APJ mRNA were quantified using real-time fluorescence quantitative PCR (RT-qPCR) methodology. The Sequential Organ Failure Assessment (SOFA) score was determined at the time of enrollment. The prognostic values of apelin-13 and APJ was evaluated in comparison to that of PCT and the SOFA score. All patients were followed up for a duration of 28 days. Results: The plasma concentrations of apelin-13 and APJ exhibited a positive correlation with the severity of sepsis, while the number of CD4+ T cells decreased in septic patients. The areas under the receiver operating characteristic (AUC) curves for apelin-13 and APJ in the diagnosis and prediction of 28-day mortality were greater than that of PCT. In non-survivors at the 28-day follow-up, the plasma levels of apelin-13 and APJ were significantly higher compared to survivors. Furthermore, apelin-13 levels were notably higher in cases of sepsis-induced cardiomyopathy (SICM) than in those without SICM. Apelin-13 and APJ emerged as independent predictors of 28-day mortality among septic patients. Conclusions: Apelin-13 and APJ demonstrate value in the assessment of risk stratification, early diagnosis, and prognosis of sepsis in the ED. Apelin-13 also proves to be an effective biomarker for assessing the prognosis of SICM in the ED. Sepsis may lead to immune function suppression.